IMPLEMENTASI PERMAINAN EDUKATIF STAIRS & CIGARETTES DALAM LAYANAN BIMBINGAN DAN KONSELING UNTUK MEMBENTUK SIKAP ANTI-MEROKOK SISWA SMA - Gusti Habibah; Muhammad Arsyad; Muhammad Andri Setiawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to determine the effectiveness of the implementation of the educational game Stairs & Cigarettes in guidance and counseling services on the formation of anti-smoking attitudes in high school students. The study used a quantitative approach with a quasi-experimental design (pretest–posttest with control group). The research subjects had a sample of 32 students consisting of two groups, namely 16 students in the experimental group based on educational games and 16 students in the control group who received guidance and counseling services without games. The research instrument was a Likert scale questionnaire compiled based on the Health Belief Model (HBM) indicators and has met the validity and reliability tests. Data analysis was performed using non-parametric tests. The results of the Mann–Whitney U test on the pretest scores showed no significant difference between the two groups (U = 108.50, Z = −0.740, p = 0.460. The Wilcoxon test showed a significant increase in anti-smoking attitudes in both groups (p < 0.001). However, the results of the Mann–Whitney U test on the posttest scores showed a significant difference between the experimental group and the control group (p < 0.001). The experimental group obtained an average N-Gain value of 53.05% (medium–high category), higher than the control group of 26.68% (low–medium category), with an effect size value of r = 0.80 (large category). Thus, it can be concluded that the educational game Stairs & Cigarettes is effective in guidance and counseling services to shape the anti-smoking attitudes of high school students.